2006
DOI: 10.1097/00003727-200601000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Home Nutrition Environment

Abstract: The specific aim for this pilot study was to evaluate the effectiveness of a nutrition and media literacy intervention targeting elementary students and their parents. The purpose of the intervention was to increase child fruit and vegetables (FV) consumption and change the home nutrition environment (measured with FV availability and accessibility and parental social support). During the intervention, students learned about nutrition, the role media plays in shaping values concerning nutrition, and developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Several of studies had multiple publications reporting results (e.g., outcomes reported at different time points): Ammerman et al [18,19,311], Bere [139,312,313]; Bere et al [140,314,315], Byrd-Bredbenner et al [146,316], Ciliska et al [15,317], Chen et al [48,318], Colby [247,319], Covelli [79,320], Cullen et al [253,321], Gortmaker et al [163,322], Haarens et al [166,323], Hendy et al [55,324], Hollar et al [96,325,326], Hopper et al [174,327], Jimenez et al [100,328,329], Latimer [273,330], Lautenschlager and Smith [275,331], Lytle et al [191,332,333], McCormick et al [285,334], Nicklas et al [198,335], Parmer et al [203,336], Reinaerts et al [217,337], Tak et al [121,338,339], Tanner et al [120,340], Taylor et al [229,341], Thomas et al [42,342], Thompson et al [231,232,343], Walker [267,303], Wardle et al [69,344], and Wrigley [306,345]. The number of citations for each study design and the reported outcome measures are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Several of studies had multiple publications reporting results (e.g., outcomes reported at different time points): Ammerman et al [18,19,311], Bere [139,312,313]; Bere et al [140,314,315], Byrd-Bredbenner et al [146,316], Ciliska et al [15,317], Chen et al [48,318], Colby [247,319], Covelli [79,320], Cullen et al [253,321], Gortmaker et al [163,322], Haarens et al [166,323], Hendy et al [55,324], Hollar et al [96,325,326], Hopper et al [174,327], Jimenez et al [100,328,329], Latimer [273,330], Lautenschlager and Smith [275,331], Lytle et al [191,332,333], McCormick et al [285,334], Nicklas et al [198,335], Parmer et al [203,336], Reinaerts et al [217,337], Tak et al [121,338,339], Tanner et al [120,340], Taylor et al [229,341], Thomas et al [42,342], Thompson et al [231,232,343], Walker [267,303], Wardle et al [69,344], and Wrigley [306,345]. The number of citations for each study design and the reported outcome measures are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…One study also used parents to recall the amount of physical activity their child(ren) participated in over a period of time [ 40 ]. Diet was similar as six studies relied on self-report [ 21 , 23 , 30 , 33 , 36 , 38 , 39 , 41 ], and three relied on parent recalls [ 29 , 34 , 40 ]. Self-report methods did vary however, with some studies utilizing surveys and others using 24-hour recalls.…”
Section: Discussionmentioning
confidence: 98%
“…During the program troop leaders served as positive role models and merit badges were given to incentivize the young girls to adopt healthy behaviors [ 38 ]. Sports that some children may not have experience with were also used to promote physical activity, including Pilates [ 23 ], soccer (for inner city youth) [ 31 ], and culturally tailored dance routines [ 37 ]. Communications was utilized in an intervention to help children learned aspects of media campaigning, in which they developed refrigerator magnets, a web site, a commercial, and a rap song to promote healthy behaviors for among their family members [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the home environment and lifestyle patterns remain understudied, and few interventions have investigated parent-led multifactorial makeovers designed to create home environments that are supportive of optimal child health and healthy child weights [1-7]. Results of studies indicate that home makeovers hold great promise for ameliorating childhood obesity [8-10]. Building upon previous work, HomeStyles was developed to help parents of young children shape or makeover (ie, change) their home environment and lifestyles to prevent childhood obesity.…”
Section: Introductionmentioning
confidence: 99%